Application of Simple Additive Weighting Method to Determine Outstanding School Principals - Haswan, Febri (Politeknik Ganesha Medan, 2019)
The principal is a teacher who is given an additional assignment to be a leader in a school, the task of the principal can regulate, control and empower the community in the surrounding area, selection of outstanding school principals, so far both the school and Kuantan Singingi District Education Office determine the outstanding headmaster does not have an application that can simplify the work in calculating the weight value to determine the principals who are pretending, the assessment carried out so far is only manual, the application of the SAW method is used to select the best alternative from a number of alternatives - each participant will be ranked from highest to lowest. The results obtained from this study are that the system built can facilitate selection, so the selection process becomes more effective, efficient and transparent.